Functional and structural insights into novel DREB1A transcription factors in common wheat (Triticum aestivum L.): A molecular modeling approach. (October 2016) - Kumar, Anuj; Kumar, Sanjay; Kumar, Upendra; Suravajhala, Prashanth; Gajula, M.N.V. Prasad
Highlights: Present study provides the first structural annotation of DREB1A TF in wheat. We identified and mapped the DREB1A-TFs on the long arm of wheat 2B chromosome. In-silico gene expression analysis revealed that the identified TaDREB1A is found to be responsive to abiotic stresses. Functional partners of TaDREB1A were predicted using protein-protein interaction and from this network analysis. This bioinformatics analysis is perhaps first of its kind where we have shown gene mapping to structure dynamics in multi-omics manner in wheat. Abstract: Triticum aestivum L. known as common wheat is one of the most important cereal crops feeding a large and growing population. Various environmental stress factors including drought, high salinity and heat etc . adversely affect wheat production in a significant manner. Dehydration-responsive element-binding (DREB1A) factors, a class of transcription factors (TF) play an important role in combating drought stress. It is known that DREB1A specifically interacts with the dehydration responsive elements (DRE/CRT) inducing expression of genes involved in environmental stress tolerance in plants. Despite its critical interplay in plants, the structural and functional aspects of DREB1A TF in wheat remain unresolved. Previous studies showed that wheat DREBs ( DREB1 and DREB2 ) were isolated using various methods including yeast two-hybrid screens but no extensive structural models were reported. In this study, we made an extensive in silico study to gain insight into DREB1A TF and reported the location of novel DREB1A in wheat chromosomes. We inferred the three-dimensional structural model of DREB1A using homology modelling and further evaluated them using molecular dynamics(MD) simulations yielding refined modelled structures. Our biochemical function predictions suggested that the wheat DREB1A orthologs have similar biochemical functions and pathways to that of AtDREB1A. In conclusion, the current study presents a structural perspective of wheat DREB1A and helps in understanding the molecular basis for the mechanism of DREB1A in response to environmental stress.